Impact of increasing the relative availability of meat-free options on food selection: two natural field experiments and an online randomised trial - Pechey, R; Bateman, P; Cook, B; Jebb, S (BioMed Central, 2022)
Background Increasing the availability of lower energy-density foods is a promising intervention to encourage healthier food purchasing but few studies have examined the effect of increasing availability of meat-free meals to promote more sustainable purchasing. We report three studies, all examining the impact of altering the availability of meat-free meals on meal selection. Methods Study 1 (a natural experiment in one university cafeteria) examined the impact of altering the ratio of meat-free meals (one meat-free and two meat, to two meat-free and one meat) on weekly sales of meals containing meat. Study 2 (a natural experiment in 18 worksite cafeterias) examined the impact on meat-free meal sales of a menu change designed to increase the availability of meat-free meals. Study 3 (an online study of 2205 UK-representative adults) compared meal selections when participants were randomised to ranges comprised of (a) one meat-free, three meat options; (b) two meat-free, two meat; or (c) three meat-free, one meat. Results Study 1 suggested a significant decrease in the proportion of sales of meat options when the availability of meat-free options increased (− 19.9 percentage points; 95%CIs:-25.2,-14.6), with no evidence of changes to meat-based meal sales in other university cafeterias during the same period. Findings from Study 2 were mixed: multilevel regressions found no evidence of an increase in meat-free meals following the menu change (2.3 percentage points; 95%CIs: − 1.3,5.9), while interrupted time-series analyses suggested sales did increase (2.3; 95%CIs: 0.4,4.2), but implementation of the planned change was limited. In Study 3 reducing meat-free options from 50 to 25% reduced participants’ selection of meat-free options (odds ratio 0.35; 95%CIs: 0.26,0.46), while increasing meat-free options from 50 to 75% increased meat-free selections (odds ratio 2.43; 95%CIs: 1.94,3.04). There was no evidence effects were moderated by gender, socioeconomic status or usual meat consumption. Conclusion Increasing the availability of meat-free options is effective at reducing meat selection and purchasing for different ratios of meat to meat-free options. The magnitude of the effect is uncertain, but with no evidence of differences in response by demographic groups when directly tested. Trial registration Study 3: Open Science Framework; https://osf.io/ze9c6; 6/8/2020.